SYSTEMATIC LITERATURE REVIEW: ALGEBRAIC THINKING SKILLS IN MATHEMATICAL PROBLEM SOLVING - Mentari Siregar, Diyan (Journal of Mathematics and Scientific Computing With Applications, 2023)
This study aims to provide a systematic picture in improving students' algebraic thinking skills in solving mathematical problems through the Systematic Literature Review (SLR) method. This research will analyze articles published between 2020 and 2024, focusing on the development, techniques used, and the influence of algebraic thinking skills in solving mathematical problems. The results of the study show that students' algebraic thinking skills are very important in building critical and creative thinking skills, which has an impact on solving complex problems effectively. The study also highlights effective learning strategies, such as cooperative approaches and technology integration, to improve algebraic thinking skills